Aneurysm of the Common Iliac Artery Revealing a Behcet's Disease - M., Elqatni; J., Fatihi; N., Elomri; M., Jira; Y., Sekkach; T., Amezyane; K., Ennibi; A., Abouzahir (Journal of Hypertension and Cardiology, 2020)
A case report of a common iliac artery aneurysm revealing underlying Behçet’s disease. It reviews diagnostic clues, vascular complications, and multidisciplinary management.
Keywords: hypertension; hypertension prevalence; systolic blood pressure (SBP); diastolic blood pressure (DBP); sodium intake; Jiangxi